Head circumference healthy male fetus after 40 weeks is greater than before week 40 - Pacora, Percy (2015)
OBJECTIVE: To establish the values of head circumference (PC) of a group of healthy newborns Lima children of women who had healthy singleton pregnancies. DESIGN: Retrospective, analytical and transversal study. MATERIALS AND METHODS: Based on maternal and perinatal data from the Department of Obstetrics and Pediatrics National Teaching Hospital Mother-Child "San Bartolome" between January 1, 1991 and December 31, 1999 (SIP) was reviewed. Singleton pregnancies of women between 20 and 30 years, with BMI between 20 and 25 km / m2 was selected healthy without obstetric complications, with difference ± 2 weeks between EG FUR and physical examination of the living and healthy newborn. RESULTS: The sound in Lima (50th percentile (10th percentile-90th percentile)) 5443 head circumference of newborns (NB) at weeks 36,36,37,38,39,40,41 and 42 were 33 (31-35 ), 33 (31-35), 34 (32 to 35.5), 34 (32-36) 34 (32-36), 34 (32.5 to 36), 34.5 (33-36) and 35 (33 to 36.5) cm, respectively. The head circumference of healthy fetuses between 48 and 41 weeks was higher in male fetuses than female fetuses (p <0.001). RN multiparous pregnant in semenas 37-41 were more cephalic that nulliparous (p <0.001) perimeter. CONCLUSIONS: The head circumference increases with gestational age and is influenced by the fetal sex and maternal parity. The cephalic perimeter of male fetuses from 40 weeks is greater than before week 40. This feature would favor cephalopelvic disproportion in the male fetus.